Dīwān-i Munjīk Tirmidhī : Ashʿār-i parākanda - Tirmidhī, Abu ʼl-Ḥasan Munjīk (Miras Maktoob, ISBN: 9789004365452., 2019)
Abu ʼl-Ḥasan Munjīk Tirmidhī was a Persian poet of the second half of 4th/10th century. Not much is known about his personal life, just that he sang the praise of some of the members of the ruling Muḥtājid dynasty of Chaghāniyān in Transoxania, a region just north of his hometown of Tirmidh. He was a contemporary of other poets at the Muḥtājid court, such as Daqīqī (d. ca. 365/976) and Farrukhī (d. before 432/1041). Tirmidhī is especially known for his panegyrics and his satire. In Nāṣir Khusraw's (d. 481/1088) Safar-nāma it is stated that Tirmidhī's divan was extant. Today his divan is lost. What verses we have were gleaned from biographical dictionaries, poetical anthologies and works on eloquence. The present edition contains a listing of everything found in such sources, supplemented by additional information taken from modern authors. The collection contains 410 verses, 50 of which were hirtherto unknown.